MOU SIGNED BETWEEN USM-MIH TO PROMOTE USM RESEARCH PRODUCTS ABROAD - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 27 April 2016 – Universiti Sains Malaysia (USM) signed a Memorandum of Understanding (MoU) recently with MyInnoHub (MIH), which is an initiative of the Ministry of Higher Education, to create an ecosystem of innovation by promoting research products of the university at the world stage.